REGULATORY FACTORS AFFECTING CHINESE COMPANIES ISSUING INITIAL PUBLIC OFFERINGS IN THE MAIN BOARD OF STOCK EXCHANGE OF HONG KONG LIMITED - Fan, W K (2008)
IPO market in Hong Kong has been prosperous during years 1999 to 2007. In particular, nearly half of the newly listed shares are China-related companies and significant over-subscriptions have been reported for many IPOs. As there is an upward trend for Chinese companies listing in Hong Kong, this dissertation is dedicated to discuss how the Chinese entities could prepare their initial public offerings ('IPO') in Hong Kong. The focus of this dissertation is to prepare the issuers to manage their IPO in Hong Kong by providing them with a brief overview of the Hong Kong stock market, including the IPO market and highlight the major regulatory requirements for listing in the Main Board ('MB') in the form of either H Share or Red Chip. This report then proceeds to suggest how Chinese issuers may secure their IPO listing successfully through re-structuring the listing vehicles. Finally, the common underwriting arrangements are introduced and the adoptions of underpricing strategy for IPOs are recommended.